Pembinaan Pembuatan Media Pembelajaran Interaktif Bagi Guru SDN 15/III Tanjung Pauh Mudik Kabupaten Kerinci: Pengabdian - Nurfazlin Nova; Nurdawani Putri Insyani; Siska Widyawati; Fitriani; Eka Puji Lestari; Berliana Dwi Kenanga; Refalia Bafadal; Ifdil Gibran (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
One of the teacher competencies that is not yet optimal is interactive teaching skills using the Canva application, due to a lack of mastery of the application. Therefore, interactive learning media training for teachers at SDN 15/III Tanjung Pauh Mudik is necessary. This training aims to improve teachers' abilities in creating Canva-based teaching media and encourage a more effective and innovative teaching and learning process. This media is expected to facilitate teachers and students in learning, resulting in more optimal learning outcomes. The activity was carried out through demonstration methods and independent practice, with four stages: planning, preparation, training and coaching, and evaluation. As a result, the training went well and met expectations, with teachers demonstrating understanding and ability in creating interactive Canva learning media for various subjects at the elementary school level.